Positive Blood Culture Results Predominantly Unrevealed among Adults Patients with Sepsis - Hursepuny, Valentine; Baedah Madjid; Firdaus Hamid; Mochammad Hatta; Muh. Nasrum Massi; Rizalinda Sjahril; Yoeke Dewi Rasita; Lisa Tenriesa; Andi Rofian Sultan (Alami Journal (Alauddin Islamic Medical) Journal, 2024)
Sepsis is increasing every year and can be life-threatening. In the diagnosis of sepsis, it is challenging to identify the causative agent of infection. This research aims to determine the proportion of positive blood culture in sepsis patients at Hasanuddin University Hospital, Makassar. Blood cultures were collected from 98 adult patients with sepsis manifestations. This research design is cross-sectional with a descriptive observation approach. The data analysed in descriptive statistics were utilised to summarise patient demographics, treatments, and outcomes. Thirteen of 98 samples were positive for microbial pathogens (13.26%). The elderly group had the highest percentage (76.5%); eighty-seven patients (88.77%) were treated with antibiotic therapy prior to blood culture collection. Cephalosporins are the most administered antibiotics (72.4%). Administration of empirical therapy prior to blood culture collection may decrease the sensitivity of culture results. The culture of the infectious focus should be done to assist in the consideration of antimicrobial treatment.